High-temperature dependence of low magnetization Mn5Ge3 phase formation of sputtered thin films (Superficies y Vacío, 2017)
We report on the high-temperature dependence of the Mn5Ge3 phase formation on Ge(001). High substrate temperatures from 650 to 850 °C lead to the formation of the Mn5Ge3 thin films with a low magnetization of ~250 kAm-1, which is an important characteristic for faster and low energy consumption of the switching of the magnetic orientation of magnetic thin films by spin-transfer torque. The highest temperature conducts to the formation of the Mn5Ge3 phase with only a small amount of Mn5Ge2 hexagonal clusters. Additionally, carbon doping of the Mn5Ge3 sample grown at 750 °C exhibits an enhancement of the Curie temperature from 296 K to 390 K. The growth mechanism corresponds to a Volmer-Weber mode.